2015
DOI: 10.1118/1.4914395
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved dosimetry using a pinpoint ionization chamber as quality assurance for IMRT and VMAT a)

Abstract: This study showed that time-resolved dosimetry using an ionization chamber is feasible and can be largely automated which limits the required additional time compared to integrated dose measurements. It provides a unique QA method which enables identification and quantification of the contribution of various error sources during IMRT and VMAT delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…However for VMAT treatments in this study, the dose to skin could be regarded as exit dose because the majority of dose to the skin was delivered through medial beam angles. Using the methodology previously developed for time-resolved point dose QC to assess the TPS calculated dose per control point [48], it could be demonstrated that ∼80% of the dose delivered to 40 superficial HD-CTV points with D acc < 95% D presc was deposited at beam angles where the effective depth was larger than or equal to 4 mm. More detail on this analysis is provided in Supplementary Material G. In general, full scatter conditions can simply be achieved by immobilization devices such as radiation masks 'behind' the patient.…”
Section: Discussionmentioning
confidence: 99%
“…However for VMAT treatments in this study, the dose to skin could be regarded as exit dose because the majority of dose to the skin was delivered through medial beam angles. Using the methodology previously developed for time-resolved point dose QC to assess the TPS calculated dose per control point [48], it could be demonstrated that ∼80% of the dose delivered to 40 superficial HD-CTV points with D acc < 95% D presc was deposited at beam angles where the effective depth was larger than or equal to 4 mm. More detail on this analysis is provided in Supplementary Material G. In general, full scatter conditions can simply be achieved by immobilization devices such as radiation masks 'behind' the patient.…”
Section: Discussionmentioning
confidence: 99%
“…ArcCHEK/MapCHECK, MatriXX with COMPASS, electronic portal imaging device, DAVID TM System, Dolphin®, Magic Plate, VANILLA, Delta4 Discover, and the double wedge-shaped ionization chamber IQM system (Casar et al, 2017;Fuangrod et al, 2016;Hoffman, Chung, Hess, Stern, & Benedict, 2017;Islam et al, 2009;Li et al, 2013;Louwe et al, 2015;Myers, Stathakis, Buckey, & Papanikolaou, 2013;Oinam, Singh, Sharma, & Goswami, 2009;Poppe et al, 2006;Björn, 2010;Sanatorium, Valley, & Kong, 2012;ScandiDos, 2016;Shimohigashi et al, 2012;Stelljes et al, 2015;Thoelking et al, 2016;Velthuis et al, 2014;Wendling et al, 2006;Wong et al, 2012;Woodruff et al, 2015). These QA systems have generally been accepted for VMAT quality assessment procedures.…”
Section: Octaviusmentioning
confidence: 99%
“…In advanced X‐ray radiotherapies, such as intensity modified radiotherapy (IMRT) and volumetric modulated arc therapy, several studies have been conducted to measure partial dose rather than an integrated dose to verify the dose at each control point (CP), which includes the gantry angle, the multileaf collimator aperture, and others. Because dose measurement is conducted over a period of seconds, this method is known as time‐resolved dosimetry (TRD) 3 . In the HIMAC system, the spots (not the CP) carry the most detailed information; therefore, the “spot” is a concept that is more closely related to the CP in IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…Because dose measurement is conducted over a period of seconds, this method is known as time‐resolved dosimetry (TRD). 3 In the HIMAC system, the spots (not the CP) carry the most detailed information; therefore, the “spot” is a concept that is more closely related to the CP in IMRT. The spots are generated for all positions within a 3D field and, the number of spots is at least two digits larger than the number of CPs in X‐ray radiotherapy (Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%